Genotoxicity Evaluation in Severe or Mild Diabetic Pregnancy in Laboratory Animals - Lima, P. H. O. [UNESP]; Sinzato, Y. K. [UNESP]; Gelaleti, R. B. [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Johann Ambrosius Barth Verlag Medizinverlage Heidelberg Gmbh, 2012)
This study aimed to evaluate the genotoxicity (DNA damage levels) in lymphocyte samples from pregnant Wistar rats with severe or mild diabetes and in whole blood samples from their newborns. Wistar female rats (1 and 90 days of age) and male rats (approximately 90 days of age) were used. The experiment consisted of 2 experimental groups (n = 8 animals/group): 1) rats with severe diabetes, 2) rats with mild diabetes. For mild diabetes induction, the rats received streptozotocin (STZ) subcutaneously (100 mg/kg body weight) at day of birth, and those showing glycemia from 120 to 300 mg/dL in their adult life were included. For induction of severe diabetes, adult rats received 40 mg/kg STZ (intravenous route), and those showing glycemia >300 mg/dL were included. At day 21 of pregnancy, the, rats were anesthetized and euthanized for removal of maternal and fetal blood samples for determination of the oxidative DNA damage by applying Endo III and Fpg using the comet assay. Thus, the rats with mild diabetes and their offspring showed higher Fpg-sensitive sites, reflecting the damage resulting from hyperglycemia. The rats with severe diabetes and their offspring showed higher oxidative DNA damage detected by Fpg and Endo III-sensitive sites, showing general repercussions related to diabetes. The enzymatic treatment for DNA damage evidenced that the maternal repercussions of diabetes are associated with oxidative DNA damage of their newborn, which was not reflected using only the analysis of DNA damage free of the enzymes.
Keywords: diabetes; DNA damage; offspring; comet assay; rat; oxidative stress